Rhipicephalus sanguineus sensu lato(Ixodidae) in synantropic rodents in Rio Grande do Sul, Brazil - Winkel,Kathleen Tavares (2014)
Rhipicephalus sanguineus, the brown dog tick, is responsible for maintaining and transmitting various pathogens, both in animals and human beings, and it is of great sanitary importance. This communication reports the first occurrence of Rhipicephalus sanguineus sensu lato parasitizing Rattus norvegicus in the state of Rio Grande do Sul, Brazil, and it is also the first record of this tick species parasitizing Rattus rattus in Brazil. The rodents were captured from the port area, located in the city of Pelotas, Rio Grande do Sul, Brazil. We collected 6 larvae of this tick species from 2 male R. rattus individuals, and 3 larvae from 2 female R. norvegicus individuals; parasitized specimens of both rodent species were captured from different sites within the experimental area. This record broadens the number of Rhipicephalus sanguineus sensu lato hosts in urban areas, indicating the need for continued monitoring on population density for both R. sanguineus and synanthropic rodents.